Identification of a HIV-1 circulating BF1 recombinant form (CRF75_BF1) of Brazilian origin that also circulates in Southwestern Europe - Bacqué, Joan; Delgado, Elena; Gil, Horacio; Ibarra, Sofía; Benito, Sonia; García-Arata, Isabel; Moreno-Lorenzo, María; de Adana, Ester Sáez; Gómez-González, Carmen; Sánchez, Mónica; Montero, Vanessa; Thomson, Michael M. (Frontiers in Microbiology, 2023)
The high recombinogenic potential of HIV-1 has resulted in the generation of countless unique recombinant forms (URFs) and around 120 circulating recombinant forms (CRFs) reported in the literature. The number of CRFs is increasing unceasingly, due to both their new generation and the identification of old previously undocumented CRFs. Those derived from subtypes B and F1 are among the most numerous, with 19 reported in the literature, most of them of South American origin.Here we show, through bootscanning and phylogenetic analyses, that two previously reported BF1 recombinant viruses from Italy analyzed in near full-length genomes (NFLG), originally described as URFs, together with two other viruses with newly derived NFLG sequences from Spain represent a new CRF, designated CRF75_BF1. CRF75_BF1 exhibits a complex mosaic structure with 20 breakpoints, which is the highest reported for any CRF. We show that CRF75_BF1 or CRF75_BF1-related viruses circulates in Italy, Spain, and Brazil, with sporadic cases found in the USA, the United Kingdom, Slovakia, and South Africa. All four patients harboring CRF75_BF1 viruses studied by us had CD4 + T-cell lymphocyte counts below 220/mm 3 less than 1 year after diagnosis, a proportion that was significantly higher (p=0.0074) than the 29% found in other patients studied in Spain by us during the same period. Through a Bayesian coalescent analysis, CRF75_BF1the emergence origin of the clade comprising CRF75_BF1 and related viruses was estimated around 1984 in Brazil, with subsequent introduction of CRF75_BF1 in Italy around 1992, and migration from Italy to Spain around 1999. CRF75_BF1 is the 6th CRF of South American origin initially identified in Western Europe, reflecting the increasing relationship of South American and European HIV-1 epidemics. The finding of low CD4 + T-cell lymphocyte counts early after diagnosis in patients harboring CRF75_BF1 viruses warrants further investigation on the virulence of this variant.